Prinsip Syariah dalam Pengelolaan Akad untuk Transaksi Ekonomi Islam - Sufiana Fahmi; Mukhtar Lutfi; Amiruddin K (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2025)
Akad is an essential element in Islamic economic transactions as it serves as the foundation of the agreement between the involved parties. The underlying principles of Sharia in managing contracts include justice, honesty, equality, and trust, with the aim of creating fair transactions in accordance with Islamic law. This article aims to examine the principles of Sharia in managing contracts and their implementation in various forms of Islamic economic transactions, such as Islamic banking, microfinance, and Shariah compliant capital markets. The qualitative approach is used with normative analysis of classical and contemporary Islamic literature, as well as a review of modern practices. The study's findings indicate that proper Shariah-compliant contract management not only ensures the legality of transactions but also enhances trust and blessings in economic activities. By understanding these principles, it is hoped that the community and economic players can implement contracts more wisely and responsibly.